ANTIBACTERIAL ACTIVITY OF A SECONDARY METABOLITE-PRODUCING CORAL BACTERIUM Pseudoalteromonas SPECIES - ocky radjasa; Torben Marten; Thorsten Brinkoff; Hans-Peter Grossart; Agus Sabdono; Meinhard Simon (JOURNAL OF COASTAL DEVELOPMENT, 2004)
A bacterium, collected at the surface of coral Acropora sp., TAB4.2 was successfully screened for secondary metabolites production based on PCR amplification of the non-ribosomal peptide synthetase gene. It was identified as closely related to Pseudoalteromonas luteoviolacea based on its 16S rDNA. TAB4.2 was found to inhibit the growth of all 5 coral-associated and all 5 pathogenic bacteria tested. To characterize the inhibiting metabolite, a 279 bp long DNA fragment was obtained and the deduced amino acid sequence showed conserved signature regions for peptide synthetases and revealed a high similarity to NosD (40 % identity), a multifunctional peptide synthetase from Nostoc sp. GSV224, and NdaB (44 % identity), a peptide synthetase module of Nodularia spumigena. m es` on their ecology. Due to this, water quality management in these ecosystems has become a necessity. Regular studies of the hydrological parameters are essential for this purpose, as they can assess the status of pollution and help in deciding the mitigation strategy. Water quality of 26 km stretch of Thane creek, central-west coast of India was analyzed in 5 regions of the creek from May 1999 to April 2000. The study revealed spatial and temporal patterns. Heavy suspended solid load (avg. 5.736 gm/L), frequent hypoxia (DO<2.5 mg/L) coupled with excess nutrients like Phosphate-Phosphorus (avg. 0.26 mg/L) and Nitrate-Nitrogen (avg. 0.96 mg/L) were the main features of the creek. The Thane city region showed more deterioration of water quality compared to the other regions in the creek. In this region the suspended solid load showed an increase of 713.69% and dissolved oxygen decreased by 21.55% compared to the data of 1992-93. This can be attributed to the severe onslaught of activities in this region like solid waste dumping, construction of 3 new bridges, etc. since 1993, thereby affecting the flushing characteristic. Hence in order to protect and preserve such ecosystems, alterations to the environment should be meticulously planned.